A new species of Parapsectrocladius Cranston (Diptera: Chironomidae: Orthocladiinae) from Patagonia, Argentina - Donato, Mariano; Mauad, Melina; Fuentes, María Cecilia (Zootaxa, 2015)
Parapsectrocladius setosus sp. n. is described and figured as pupa and male imago, based on material collected in Patagonia, Argentina. The male of the new species groups with P. escondido Cranston & Añón Suárez by having the anal point tapering triangular; inferior volsella simple, rounded, without any dorsal ridge and apically blunt. It can be distinguished from P. escondido by the possession of strong setae on the inner margin of inferior volsella. New material of Parapsectrocladius belonging from several localities allows us to emend the generic diagnosis of the adult male, female and larva of Parapsectrocladius, discuss its phylogenetic position and to expand the geographic distribution of P. acuminatus Cranston, P. escondido and P. reissi. Cranston.